Cost efficiency of insurance firms in Ghana - Danquah, M.; Otoo, D.M.; Baah-Nuakoh, A. (Managerial and Decision Economics, 2018)
The huge infrastructural deficit in Africa requires the establishment of an efficient insurance industry in the pursuance of economic development. Unfortunately, global statistics reveal low patronage of insurance in developing countries, thus making its impact limited in the region. To position the industry for economic development, this study utilizes the stochastic frontier technique to undertake a thorough analysis on the cost efficiency of insurers from the perspective of developing economies using Ghana as a case study. The results on the 30 insurers studied from 2005 to 2014 indicate that insurers in Ghana operate with about 53.8% average cost inefficiency. This stands to confirm the long existed low performance perception of Ghanaians about the industry. Factors identified to explain the cost inefficiencies were firm size, market share, capitalization, reinsurance, regulation, and business type. Several policy recommendations that can help boost the cost efficiency of insurers were derived from the results.